Banking relationships and access to equity capital markets: evidence from Japan's main bank system - Kenji Kutsuna; Janet Kiholm Smith; Richard L. Smith (Claremont McKenna College, Department of Economics, 2005)
We study the role of banking relationships in IPO underwriting. Among other issues, we consider whether banking relationships lead to increased access to public equity markets, especially for smaller, lesserknown firms. When a firm in Japan goes public, it can engage an investment bank that is related through a common main bank, or can select an alternative investment bank. The main bank relationship can be an efficient way for the investment bank to acquire information generated by the main bank, but may give rise to conflicts of interest. We use data from two different investment banking regimes in Japan (a hybrid auction-method regime and a book-building regime) and find that main bank relationships give small issuers increased access to equity capital markets, but that issuers of large IPOs switch to non-related investment banks that are capable of managing large offerings. While we find evidence that investment banks seek to exploit bargaining power with related issuers, we also find that issuers respond to expected high issue cost by switching to non-related investment banks. The net result is that total issue costs through related and non-related investment banks are similar. With respect to aftermarket performance and use of offer proceeds, we find no evidence of conflict of interest or self-dealing for either the main bank or the investment bank.
Keywords: G21; G24; L22; L51; 330; Main Bank; Banking Relationships; Capital Market Access; IPOs; Underwriting; Japanese Economy; Bank; Business Network; Investment Bank; Wertpapieremission; Eigenkapital; Japan